Demographic expansion and genetic load of the halophyte model plant Eutrema salsugineum - Wang, Xiao-Juan; German, Dmitry (Molecular ecology, 2018)
The halophyte model plant Eutrema salsugineum (Brassicaceae) disjunctly occurs in temperate to subarctic Asia and North America. This vast, yet extremely discontinuous distribution constitutes an ideal system to examine long-distance dispersal and the ensuing accumulation of deleterious mutations as expected in expanding populations of selfing plants. In this study, we resequenced individuals from 23 populations across the range of E. salsugineum. Our population genomic data indicate that E. salsugineum migrated "out of the Altai region" at least three times to colonize northern China, northeast Russia and western China. It then expanded its distribution into North America independently from northeast Russia and northern China, respectively. The species colonized northern China around 33.7 thousand years ago (kya) and underwent a considerable expansion in range size approximately 7-8 kya. The western China lineage is likely a hybrid derivative of the northern China and Altai lineages, originating approximately 25-30 kya. Deleterious alleles accumulated in a stepwise manner from (a) Altai to northern China and North America and (b) Altai to northeast Russia and North America. In summary, E. salsugineum dispersed from Asia to North America and deleterious mutations accumulated in a stepwise manner during the expansion of the species' distribution.
Gesehen am 19.06.2019